OPTIMALISASI PENULISAN KARYA ILMIAH TUGAS AKHIR BERBASIS LITERASI DIGITAL MELALUI PELATIHAN MANAJEMEN REFERENSI ZOTERO PADA MAHASISWA SASTRA UNIVERSITAS NAHDLATUL WATHAN MATARAM - Ahmad Sirojul Hakiki; Mugni; Muhammad Dedad Bisaraguna Akastangga; Zamroni; Lalu Abdul Razak Hazami; Ahmad Hizkil; Nofi Fitria Indasari; Masdani; Budi Ilham (DEVELOPMENT: Journal of Community Engagement, 2026)
The paucity of knowledge regarding academic citations in the digital era of 5.0, which has undergone a comprehensive digital transformation across all domains, including the domain of academic writing, has not been adequately addressed by the knowledge of literary studies at the University of Mataram. Consequently, the process of producing academic papers in the context of citations still relies on conventional methods. This has resulted in a significant number of errors in the writing process. In light of these issues, a PKM was organised to provide training in the use of Zotero, a tool designed to facilitate the process of referencing in academic writing. The process is comprised of several stages. Firstly, planning is undertaken, which includes the following: initial observation, interviews, a pre-test, and creation of a module. Secondly, the implementation stage is initiated, which includes the delivery of materials, the posing of questions, and practical exercises. These practical exercises include the installation of Zotero, downloading articles, and inserting articles into Zotero. Finally, the process is concluded with a review. The results of the study, as measured by the Zotero software, demonstrate a significant increase in the post-test results. In general, 25 out of 30 participants (83.3%) successfully utilised Zotero. However, the remaining five participants (16.7%) were unable to complete the full installation and practical processes due to insufficient processing power.